Efektivitas Model Pembelajaran Missouri Mathematics Project Menggunakan Strategi Think Talk Write Berbantuan LKPD terhadap Kemampuan Pemecahan Masalah - Sulistyani, Sulistyani; Franita, Yesi; Pradanti, Paskalia (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
The purpose of this study was to analyze the classical completeness of students' problem solving ability by using Missouri Mathematics Project learning model using Think Talk Write strategy assisted by LKPD and direct learning model, and to analyze the effectiveness of Missouri Mathematics Project learning model using Think Talk Write strategy assisted by LKPD compared to direct learning model on students' problem solving ability.    This research was a quantitative research with quasi experimental research design in the form of nonequivalent post-test only control group design. The sampling technique in this study was cluster random sampling. The research instruments were interview guidelines, observation sheets, problem solving ability tests, and validation sheets. Data collection techniques in this study were interviews, observations, problem solving ability tests, validation questionnaires, and documentation. The experimental class proportion test results with  and  and the control class with  and . This showed that  so that  was accepted, meant that students who were taught using the Missouri Mathematics Project model using the Think Talk Write strategy assisted by LKPD and the direct learning model achieved classical completeness. Then, the results of the independent sample t-test showed that  and , then  so that  was rejected, meant that the Missouri Mathematics Project learning model using the Think Talk Write strategy assisted by LKPD was more effective than the direct learning model on students' problem solving skills.